2007
DOI: 10.1007/s12033-007-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

ASK Family Proteins in Stress Response and Disease

Abstract: Cells are continuously exposed to reactive oxygen species (ROS) generated by aerobic metabolism. Excessively generated ROS causes severe dysfunctions to cells as oxidative stress. On the other hand, there is increasing evidence that ROS plays important roles as a signaling intermediate that induces a wide variety of cellular responses such as proliferation, differentiation, senescence, and apoptosis. To transmit physiological ROS-mediated signals and to adapt to oxidative stress, cells are equipped with variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 27 publications
(28 reference statements)
2
41
1
2
Order By: Relevance
“…This is in good agreement with the known fact that ASK1 is a member of the MAPKKK family preferentially activated by various cytotoxic stresses (19,27) and plays a causal role in cell death induced by a number of stimuli (18). Activation of ASK1 has been shown to be often mediated by ROS (19,27,54,55). The present study also demonstrated that ASK1 phosphorylation induced by STS, TNF␣, and FasL was dependent on ROS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in good agreement with the known fact that ASK1 is a member of the MAPKKK family preferentially activated by various cytotoxic stresses (19,27) and plays a causal role in cell death induced by a number of stimuli (18). Activation of ASK1 has been shown to be often mediated by ROS (19,27,54,55). The present study also demonstrated that ASK1 phosphorylation induced by STS, TNF␣, and FasL was dependent on ROS.…”
Section: Discussionsupporting
confidence: 92%
“…*, p Ͻ 0.05 versus isotonic. natively termed protein kinase B, and apoptosis signal-regulating kinase 1 (ASK1), a Ser/Thr-protein kinase that belongs to the MAPKKK family because of the following previous observations: Modulation of Akt by a hypertonic stimulation (16) was opposite to that by an apoptotic stimulation (17) in renal epithelial Madin-Darby canine kidney cells, and ASK1 was inhibited by Akt in L929 cells (18) and activated by a variety of apoptotic stimuli in a number of cell types (18,19). The present study demonstrates that in human epithelial HeLa cells shrinkage-induced activation of Akt1 is involved in the RVI process and that ASK1-induced inhibition of Akt1 activation causes inhibition of RVI in apoptotic HeLa cells.…”
mentioning
confidence: 99%
“…We tested the expression of apoptosis-regulating genes Traf2, Traf6, Parp1, Atf6, Ask1, Ask2, Dapk1, and Apaf1 in siBrg1 NCCs (21)(22)(23)(24)(25)(26)(27)(28). Of these genes, only Ask1 (apoptosis signal-regulating kinase 1) exhibited increased expression (a 1.65-fold increase; P < 0.03) in siBrg1NCCs; the other genes showed no significant changes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…22 In nonerythroid cell models, ROS have been reported to induce apoptosis by activating apoptosis signal regulating kinase 1 and jun-kinase; this mechanism may contribute to erythroid cell apoptosis in thalassemia. 36 In addition, there is evidence that apoptosis in thalassemic red blood cells is mediated by the Fas cell surface death receptor (FAS) and FAS-ligand pathway, which is triggered by high levels of ROS. 37 A recent study has demonstrated that heat shock protein 70 interacts directly with free a-globin chains, and thereby becomes sequestered in the cytoplasm.…”
Section: 21mentioning
confidence: 99%